2016
DOI: 10.2215/cjn.04150415
|View full text |Cite
|
Sign up to set email alerts
|

High Dose Omega-3 Fatty Acid Administration and Skeletal Muscle Protein Turnover in Maintenance Hemodialysis Patients

Abstract: Background and Objectives Protein energy wasting and systemic inflammation are prevalent in maintenance hemodialysis (MHD) patients. Omega-3 (v-3) fatty acids have anti-inflammatory properties and have been shown to improve protein homeostasis. We hypothesized that administration of high-dose (2.9 g/d) v-3 would be associated with decreased muscle protein breakdown in MHD patients with systemic inflammation.Design, setting, participants & measurements This is a substudy from a randomized, placebo-controlled st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…No difference was observed in FBG, LDL, homeosis model assessment insulin resistance (HOMA-IR), insulin, leptin or adiponectin [ 21 ]. No effects of higher doses of omega 3 FA (1914 mg EPA and 957 mg DHA daily supplementation compared to placebo for 12 weeks), were also observed for FBG level and HOMA-IR [ 22 ]. A small dose of omega 3, consisting in 80 mg EPA and 120 mg DHA daily for 10 weeks, was compared with a placebo condition using vit E [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…No difference was observed in FBG, LDL, homeosis model assessment insulin resistance (HOMA-IR), insulin, leptin or adiponectin [ 21 ]. No effects of higher doses of omega 3 FA (1914 mg EPA and 957 mg DHA daily supplementation compared to placebo for 12 weeks), were also observed for FBG level and HOMA-IR [ 22 ]. A small dose of omega 3, consisting in 80 mg EPA and 120 mg DHA daily for 10 weeks, was compared with a placebo condition using vit E [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, it indicated that the change of serum CRP level was not different among the two groups. In another study performed by Himmelfarb et al, serum CRP data were expressed in the form of a histogram, and it also indicated no significant difference in the treatment and control group .…”
Section: Resultsmentioning
confidence: 97%
“…These 12 studies included a total of 487 patients, among which 254 were treated with omega-3 fatty acids and a control group included 233 treated with placebo. These studies also provided the outcomes reflected in the levels of CRP (22,(25)(26)(27)(28)(29)(30)32,33,35), IL-6 (25,(29)(30)(31)(32)(33)35) and TNF-α (29,31,32,34). Among these, four studies included CKD patients who did not receive dialysis (22,27,31,34).…”
Section: Characteristics Of Included Studies and Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations